(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article offers a comprehensive exploration of pesticide utilization in vineyards and the quantitative assessment of carbohydrate levels in grapes. Emphasizing strategies to mitigate grape pests and diseases, it delves into the correlation between pest management practices and sugar content in grapefruits. By scrutinizing these intertwined aspects, this study aims to elucidate the intricate dynamics shaping vineyard management strategies and the nutritional composition of grapes. Through an amalgamation of scientific insights and practical considerations, this research contributes to the ongoing discourse surrounding sustainable viticultural practices and the promotion of grapefruit quality.